1990
DOI: 10.1063/1.458871
|View full text |Cite
|
Sign up to set email alerts
|

The influence of potential energy surface topologies on the dissociation of H2

Abstract: In this work we present a theoretical study of the dissociative adsorption of hydrogen molecules from a series of model potential energy surfaces. The aim is to discover those particular topological features in the potential surface which are responsible for determining the vibrational state-to-state cross sections in both the dissociated and the scattered flux. The potential energy surface is two-dimensional, and is chosen to be deliberately simple; a combination of Morse potentials and a Gaussian barrier. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(65 citation statements)
references
References 36 publications
1
64
0
Order By: Relevance
“…Work done on the H 2 ϩCu system and aimed at calculating the ''threshold'' or ''barrier'' to the reaction includes experiments, 1-11 electronic structure calculations, [12][13][14][15][16][17][18][19] and dynamical studies. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] The experimentally obtained reaction probabilities or sticking coefficients can be interpreted in terms of reaction thresholds, which are related to the barrier height obtained from electronic structure studies in a nontrivial way. 33,36 Tested against experiment, dynamics studies are the ultimate test of the accuracy of proposed potential energy surfaces ͑PES's͒, in addition to being helpful in interpreting the experimental findings.…”
Section: Introductionmentioning
confidence: 99%
“…Work done on the H 2 ϩCu system and aimed at calculating the ''threshold'' or ''barrier'' to the reaction includes experiments, 1-11 electronic structure calculations, [12][13][14][15][16][17][18][19] and dynamical studies. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] The experimentally obtained reaction probabilities or sticking coefficients can be interpreted in terms of reaction thresholds, which are related to the barrier height obtained from electronic structure studies in a nontrivial way. 33,36 Tested against experiment, dynamics studies are the ultimate test of the accuracy of proposed potential energy surfaces ͑PES's͒, in addition to being helpful in interpreting the experimental findings.…”
Section: Introductionmentioning
confidence: 99%
“…This was unexpected because vibrational enhancement is usually associated with late barriers. 6,7 However, our analysis showed that in the entrance channel the force constant associated with the vibration decreased as the molecule approached the barrier. The vibrational energy that is released in this process can flow into translation along Z, thereby enhancing reaction.…”
Section: Introductionmentioning
confidence: 81%
“…2͒ calculations. It is not due to a reduced mass effect 7 because the barriers where reaction will predominantly occur ͑barriers for the parallel orientation͒ are all located in the entrance channel. Instead vibrational enhancement is due to a decrease of the force constant associated with the molecular vibration, as the molecule approaches the barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Note that the theory underestimates the experimental vibrational efficacy because the energy shift between the laser-off and the ν 1 -excited reaction probability curves is lower for the AIMD results than that for the experiments. One reason for this 50 could be that the barrier obtained with the PBE functional occurs at a too small value of the length of the breaking bond, as also found for H 2 + Cu(111). 41 The ratio between CH and CD bond cleavage is, within the error bars of the calculations, equal to the statistical value of 1:3 for laser-off beams, but only CH cleavage is observed when the CH stretch is pre-excited (Table 2).…”
mentioning
confidence: 97%